2020
DOI: 10.1111/apt.15997
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: a history of smoking is not associated with a higher risk of pouchitis

Abstract: Summary Background Ileal pouch‐anal anastomosis is a common surgical procedure in patients with an initial diagnosis of ulcerative colitis or indeterminate colitis. Tobacco smoking has been associated with protection from onset of ulcerative colitis. Smoking has been reported to be both a protective factor and a risk factor for the development of pouchitis. Aim To examine the influence of smoking on the risk of pouchitis. Methods We identified 15 studies evaluating smoking as a risk factor for developing pouch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Our outcomes occurred in a single IBD center. Given that this was a retrospective study, we did not have accurate data regarding smoking or the presence of extraintestinal manifestations of UC at the time of colectomy, both of which have been evaluated as risk factors for pouchitis [29, 30]. We also did not evaluate the use of immunosuppressive or biologic therapies in the post-IPAA period, which could have influenced the development of pouch inflammation or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our outcomes occurred in a single IBD center. Given that this was a retrospective study, we did not have accurate data regarding smoking or the presence of extraintestinal manifestations of UC at the time of colectomy, both of which have been evaluated as risk factors for pouchitis [29, 30]. We also did not evaluate the use of immunosuppressive or biologic therapies in the post-IPAA period, which could have influenced the development of pouch inflammation or other complications.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Metaanalyse von Kani et al. hat ergeben, dass Rauchen weder einen schädigenden noch einen schützenden Effekt auf die Entwicklung einer Pouchitis hat [ 38 ].…”
Section: Darmunclassified
“… 104 A meta-analysis of 15 studies evaluating current, former, or never smokers found no association of smoking status with risk of development of pouchitis in patients with an IPAA. 16 Patients should be counseled that smoking is not recommended to prevent or treat pouchitis.…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…14 Increasingly, it is being recognized that the inflammation of pouchitis appears similar to ulcerative colitis. 15 Definitions of pouchitis vary by study, 16 including a combination of criteria based on symptoms, pouchoscopy findings, or histologic features. The most commonly use scoring system for pouchitis is the Pouchitis Disease Activity Index (PDAI).…”
Section: Introductionmentioning
confidence: 99%